The Diversity of Cyanobacteria at Ranchan Waterfall and Toxicity Assessment by using High Performance Liquid Chromatography - Nurafiqah, Binti Mohd Adzami (Universiti Malaysia Sarawak (UNIMAS), 2014)
Cyanobacteria are microscopic algae known as blue-green algae and can undergo photosynthetic process. A study was carried out to identify the diversity of Cyanobacteria at Ranchan waterfall and Toxicity Assessment by using High Performance Liquid Chromatograhy (HPLC) at three different stations. The identification of cyanobacteria was conducted by using compound microscope. There are 41 genera of cyanobacteria was present at Ranchan waterfalls and out of this genera, only eleven genera of cyanobacteria was identified as potential toxin-producer which are Aphanizomenon, Cylindrospermopsis, Cylindrospermum, Lyngbya, Microcystis, Oscillatoria, Planktothrix, Pseudanabaena, Scytonema, Synechoccoccus, and Tolypothrix. As cyanobacteria can produce cyanotoxin that can cause harmful or health effects on human and other organism in this world, and the screening of cyanotoxin by using HPLC was conducted. In this study, there is negative result detected with standard microcystin-LR from the previous study as no culture technique was done in this experiment.